Sex disparities in premature adult mortality in Estonia 1995–2016: a national register-based study - Hajo Zeeb; Kaja Rahu; Mati Rahu (BMJ Open)
Objectives To quantify sex disparities in cause-specific premature adult mortality in Estonia, to determine the causes of death with the largest differences, to provide insight into related behaviours and to offer some guidance to public health policy-makers based on the results of the study.Design A national register-based study.Setting Estonia.Data Individual records of deaths at ages 20–69 years in 1995–2016 from the Estonian causes of death register; data on tobacco smoking and alcohol consumption in the adult population in 1996–2016 from the biennial postal survey of health behaviour.Main outcome measures Overall and cause-specific age-standardised mortality rates, average annual percentage changes in mortality, and cause-specific men-to-women mortality rate ratios were calculated. In addition, the age-standardised prevalence proportions of tobacco smoking and alcohol consumption and men-to-women prevalence rate ratios were determined.Results Overall premature adult mortality decreased considerably during 1995–2016, but no reduction was observed with respect to the large relative sex disparities. In circulatory disease mortality, the disparities widened significantly over time. Extremely high mortality rate ratios were observed for cancer of the upper aerodigestive tract and for lung cancer. There was a stable, more than fivefold male excess mortality from external causes. A fourfold male disadvantage was evident for alcohol poisoning, mental disorders due to alcohol and alcohol-related degeneration of the nervous system as a group. The prevalence of tobacco smoking and harmful alcohol consumption among men exceeded that among women by factors of two and six, respectively.Conclusions Even though premature adult mortality has markedly decreased over time, there has been no success in diminishing the large sex differences in the mortality patterns, mostly associated with smoking and excessive alcohol consumption, both more prevalent among men. Estonia needs a comprehensive and consistent alcohol policy while maintaining and further developing antitobacco measures.